1997
DOI: 10.1093/ajcn/66.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of body composition measured by dual-energy X-ray absorptiometry in Dutch children and adolescents

Abstract: Knowledge about body composition is important in metabolic and nutritional studies. In this cross-sectional study the body composition of 403 healthy white Dutch children and adolescents was evaluated by using dual-energy X-ray absorptiometry (DXA). Possible determinants of body composition were analyzed. In 85 subjects the results of bioelectrical impedance analysis (BIA) were compared with DXA. Fat mass, lean tissue mass, and bone mineral content were greater in older boys and girls. Percentage body fat was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
0
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(159 citation statements)
references
References 26 publications
9
143
0
7
Order By: Relevance
“…23 The correlation of BMI to PBF has been described differently in other studies. 24 In this study in obese young subjects the overall correlation of BMI and PBF was signi®cant (for all, r 0.65; girls, r 0.68, boys, r 0.63), which is almost identical to the results presented by Pietrobelli et al in normalweight children and adolescents. 25 In our study the degree of obesity was far beyond the 95th percentile of BMI.…”
Section: Bmi and Fatness In Children K Widhalm Et Alsupporting
confidence: 90%
“…23 The correlation of BMI to PBF has been described differently in other studies. 24 In this study in obese young subjects the overall correlation of BMI and PBF was signi®cant (for all, r 0.65; girls, r 0.68, boys, r 0.63), which is almost identical to the results presented by Pietrobelli et al in normalweight children and adolescents. 25 In our study the degree of obesity was far beyond the 95th percentile of BMI.…”
Section: Bmi and Fatness In Children K Widhalm Et Alsupporting
confidence: 90%
“…In a cross-sectional study, %BF increased with age in girls only. 40 As %BF is increased in older girls, associations between macronutrients and adiposity might be stronger in girls aged 9 ± 10 y, 10 like in our study, than in younger girls.…”
Section: Discussionsupporting
confidence: 60%
“…The 95th centiles for our population are higher than those previously reported. 19 We found that the reference 95th centile for BMI corresponded to a PBF value of 37.7% for females and 32.2% for males. In this study we used BIA to determine PBF and have previously shown that BIA is more accurate than anthropometry at predicting PBF.…”
Section: Discussionmentioning
confidence: 61%